Levetiracetam Prophylaxis Therapy for Brain Tumor-Related Epilepsy (BTRE) Is Associated With a Higher Psychiatric Burden - Dono, Fedele; Consoli, Stefano; Evangelista, Giacomo; Ricci, Annalisa; Russo, Mirella; Carrarini, Claudia; Di Iorio, Angelo; Bonanni, Laura; Anzellotti, Francesca; Onofrj, Marco; Sensi, Stefano L. (Frontiers in Neurology, 2022)
Purpose: Brain tumor-related epilepsy (BTRE) is a condition characterized by the development of seizures in the context of an undergoing oncological background. Levetiracetam (LEV) is a third-generation ASM widely used in BTRE prophylaxis. The study evaluated LEV neuropsychiatric side effects in BTRE prophylaxis. Method: Twenty-eight patients with brain tumors were retrospectively selected and divided into two groups: patients with an ascertained diagnosis of BTRE on ASM (BTRE group) and patients with brain tumors who never had epilepsy and were on prophylactic ASM (PROPHYLAXIS group). Neuropsychiatric side effects (SE) of ASM were monitored using the Neuropsychiatric Inventory Questionnaire (NPI-Q) at the baseline visit and the 6-month and 12-month follow-up. Result: 18 patients of the BTRE group and 10 patients of the PROPHYLAXIS group were included. Compared to the BTRE group, the PROPHYLAXIS group showed a higher severity of neuropsychiatric symptoms. According to Linear Mixed Models, a multiplicative effect for the interaction between group-treatment and time was observed. For the caregiver distress score (CDS), only a Time-effect was observed. Conclusions: Prophylactic ASM with LEV is associated with an increased frequency of neuropsychiatric SE. An accurate epileptological evaluations in patients with brain tumors is mandatory to carefully select who would benefit most from ASM.